2022
DOI: 10.1684/ejd.2022.4202
|View full text |Cite
|
Sign up to set email alerts
|

Skin manifestations in patients with COVID-19: a prospective observational study during the first wave of the pandemic in the UK and review of the recent literature

Abstract: Background COVID-19 (SARS-CoV-2) is a viral infection that presents in heterogeneous forms with effects on multiple organ systems including the skin. Objectives The objectives of this prospective observational study were to identify cutaneous lesions in confirmed COVID-19-positive patients admitted to a district general hospital in the eastern region of England, to determine the prevalence of these lesions and compare the findings with the current literature. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Mg2+ is an important cation and coenzyme involved in enzymatic reactions [ 23 ]. Studies have shown that Mg2+ is considered the second messenger of insulin and plays an important role in glucose metabolism stability and insulin sensitivity: i) Mg deficiency reduces insulin receptor activity, leading to insulin resistance and ii) hypomagnesemia inhibits glucose utilization in basal and insulin-stimulated states [ 24 ]. The inconsistent results may be due to the small sample size of women with GDM and differences among participants.…”
Section: Discussionmentioning
confidence: 99%
“…Mg2+ is an important cation and coenzyme involved in enzymatic reactions [ 23 ]. Studies have shown that Mg2+ is considered the second messenger of insulin and plays an important role in glucose metabolism stability and insulin sensitivity: i) Mg deficiency reduces insulin receptor activity, leading to insulin resistance and ii) hypomagnesemia inhibits glucose utilization in basal and insulin-stimulated states [ 24 ]. The inconsistent results may be due to the small sample size of women with GDM and differences among participants.…”
Section: Discussionmentioning
confidence: 99%